Strategi Pencegahan Kekerasan Seksual melalui Penguatan Spiritualitas Qur’ani dan Maqamat Sufi - Achmad Yasin; Noorhidayat; Ahmad Mujahid (Jurnal Riset Multidisiplin Edukasi, 2026)
Sexual violence is a form of crime that damages human dignity, integrity and psychological health. This research offers a strategy for preventing sexual violence through strengthening qur'anic spirituality and sufi maqamat by examining a number of relevant Al-Qur'an verses as well as sufistic interpretations in the book Al-Bahr al-Madid fi Tafsir al-Qur'an al-Majid by Ibn'Ajibah. The findings show that qur'anic principles such as ghadl al-bashar (lowering gaze), al-afaf (maintaining personal purity), al-taqwa (divine awareness), and the prohibition of approaching adultery, have a strong preventive function in forming spiritual and moral character. Ibn Ajibah views controlling the nafs, cleansing the heart, and internalizing divine consciousness as prerequisites for preventing deviant behavior, including sexual violence. Through the integration of qur'anic values with sufi maqamat such as wara, iffah, patience, muraqabah, and ihsan, prevention strategies are not only normative-legalistic in nature, but also encourage individual psychological and spiritual transformation. This approach offers a comprehensive alternative paradigm and is centered on inner cultivation as the foundation for creating a social environment that is safe, ethical, and free from sexual violence.